Revealing the past: How science is unlocking cartographic secrets - Millea, N; Howell, D (Springer, 2017)
Although advanced imaging and analytical techniques have long been available, it is only over the last three to five years that they have been more generally applied to serious study of library materials. This has been driven by incredible advances in technology which allow for non-invasive, non-sampling, non-contact methods to be designed specifically with the curators’ concerns for the safety of the material in mind. At the same time the curators’ increasing awareness of what is possible has increased the demand for such services. For maps, one of the outstanding developments has been hyperspectral imaging. This is a technique where an item is scanned and each ‘pixel’ represents a full colour spectrum, commonly 400-1000 nm. The large files produced in this way can be interrogated by sophisticated software to reveal erasures and obscured areas of detail invisible to the naked eye. Hyperspectral imaging can also be used for identifying pigments, especially organic materials. This technique is completely safe if applied correctly and with continuous dialogue between curators, conservators and the people carrying out the analysis/imaging. It is now possible to employ science to date cartographic material, and to infer where maps might have been made. We can also use hyperspectral imagery to reveal underlying cartographic content previously obscured from view. This paper will examine how these techniques have been employed with varying degrees of success on the late medieval Gough Map of Great Britain, and two manuscript English estate maps, all items held within the Bodleian Library’s collections.